Endorsement in Advertising Indigenous Products and Patronage of Innoson Motors and Dangote Cement Brands in FCT, Abuja - Mgbede, Efu; Kente, J. S.; Ugande, Anthony (Lembaga Yasin AlSys, 2025)
This study investigates the role of endorsement in advertising indigenous products, focusing on consumer patronage of Innoson Motors and Dangote Cement brands in Abuja, Federal Capital Territory (FCT). Anchored on the Hierarchy of Effects Model, the research employed a survey design with a population of 3,840,000 and a sample size of 400 respondents, using questionnaires as the primary instrument of data collection. The findings reveal that 59% of respondents consider celebrity endorsement effective in promoting indigenous products by enhancing brand popularity, increasing patronage, and fostering a sense of pride in supporting locally made goods. Additionally, the study highlights that multiple factors shape consumer perceptions of indigenous products endorsed by celebrities. The study concludes that public trust in celebrities significantly influences consumer choices, with endorsement often translating into increased patronage. It recommends that celebrities engaged as brand ambassadors should maintain credibility and avoid scandals to preserve positive brand perception and strengthen consumer confidence in indigenous products.